Housing accessibility and its associations with participation among older adults living with long-standing spinal cord injury. (4th March 2017) - Norin, Lizette; Slaug, Björn; Haak, Maria; Jörgensen, Sophie; Lexell, Jan; Iwarsson, Susanne
Abstract : Objectives : To describe the housing situation and aspects of participation among older adults living with long-standing spinal cord injury (SCI) with attention to SCI severity, and to examine whether and how objective housing accessibility (based on objectively measurable criteria) is associated with aspects of participation. Design : Cross-sectional study utilizing the assessment tools Impact on Participation and Autonomy (IPA) and Housing Enabler (HE). Adjusting for demographic, social and injury related data, associations between objective housing accessibility and aspects of participation were analyzed by means of ordinal regression models. Setting : Home and community settings. Participants : Older adults (≥ 50 years) ( N   =  123), with a traumatic or non-traumatic SCI for at least 10 years. To make comparisons within the sample, three groups of SCI severity were formed using the American Spinal Injury Association (ASIA) Impairment Scale. Results : Housing adaptations and environmental barriers were common and differed between SCI severity groups; those with AIS D injuries had fewer adaptations and more environmental barriers indoors. A majority of the participants in the total sample perceived their participation as good or very good in most of the IPA activities studied. Accessibility indoors was significantly associated with autonomy indoors (P = 0.009), family role (P = 0.002) and participation problems (P = 0.004); more accessibility problems were associated with less participation and more participation problems. Conclusion : This study indicates that optimizing the housing environment for older adults with SCI can potentially increase their participation and make them more autonomous. Further studies based on longitudinal data are needed to determine the causality of the associations identified.